Phase behaviour of DPPC/Lyso-PPC mixtures by spin-label ESR and spectrophotometry. Issue 2 (2008) - Pantusa Pantusa, Manuela Manuela; Sportelli Sportelli, Luigi Luigi; Bartucci Bartucci, Rosa Rosa
Abstract : The influence of lysopalmitoylphosphatidylcholine (Lyso-PPC) on lamellar dispersions of dipalmitoylphosphatidylcholine (DPPC) has been investigated by spectrophotometry and electron spin resonance (ESR) of spin-labelled phosphatidylcholine at the C-5 or at the C-16 positions in the sn -2 acyl chain (5- and 16-PCSL). On increasing the concentration of Lyso-PPC up to 10 mol%, the spectral anisotropy of 5-PCSL is slightly reduced whereas that of 16-PCSL is markedly increased. This effect of the lysolipid on the DPPC lipid chain mobility is evident from 10 to 50 mol% at low temperature in the gel phase, disappears in the fluid phase, is associated with the lack of the pre-transition in the mixed lipid dispersions and it is interpreted as interdigitation of the DPPC lipid chains. At intermediate concentrations and for temperatures in the gel phase, the ESR spectra of both labels in DPPC and Lyso-PPC mixtures are the superposition of an anisotropic lamellar component and of an isotropic micellar signal, suggesting the coexistence of lamellar and micellar aggregates. Chain interdigitation and lamellar-micellar coexistence are not evident for temperature above the melting transition temperature. At high Lyso-PPC content (≥60 mol%) the mixed lipid dispersions reach the optical clarity, the main transition is no more detected and spin-label ESR spectra typical of micellar dispersions are detected in the whole temperature range investigated.